Human factors and ergonomics at time of crises: the Italian experience coping with COVID-19. (28th May 2020) - Albolino, Sara; Dagliana, Giulia; Tanzini, Michela; Toccafondi, Giulio; Beleffi, Elena; Ranzani, Francesco; Flore, Elisabetta
Abstract: Several of the key organizational issues that we have had to face with the emergence of COVID-19 crisis are related to human factors/ergonomics (HFE) and the safety culture. During the crisis the main activities of the healthcare services have been profoundly affected. Patient safety and risk management units have also experienced the need to adapt rapidly. What can we do as HFE experts, now that the scenario has completely changed? We contend that: (a) we can favour and support the heuristics that are applied to manage the load of psycho-cognitive stress. (b) We can observe, collect strategies and develop analytic schemes, thereby creating a memory of the organization for improvement in the future. (c) And we can support in educating and engaging the public. This crisis has forced the community of healthcare experts to broaden their reflections: for the future to come, our communities of experts in the field of risk management HF/E, quality and safety of care and public health should play together an important role from the very beginning, from the time of peace.